TEM Studies of ZnS Nanoparticles Obtained by Wet Chemical Reaction - Di Stefano, M. C. (2010)
ZnS is a useful II-VI compound for optical devices. Due to its strong fluorescence and high resistance to electric fields, it is a material with interesting applications for solar cells, IR windows, lasers and sensors. ZnS has a low excitonic Bohr radius (2.5 nm) so their nanoparticles are appropriate to produce small bio-molecular probes for fluorescence and laser scanning microscopy. Despite progress in the synthesis of the nanocrystalline ZnS many unresolved problems still remain. The origin of the visible luminescence, besides the band gap emission observed in many nanoparticles is still uncertain. In this work, ZnS nanocrystals were obtained by a wet chemical reaction. The reagents used were ZnCl2.2H2O and thiourea respectively for Zn and S. The surfactant agent was 20% tetrametylammonium hydroxide (TMAH) and the solvent was ethylene glycol. The reaction aliquots were collected for various periods of time starting from the onset of the synthesis and redispersed in methanol for optical characterization. The samples were studied by transmission electron microscopy (TEM). The X-ray diffraction (XRD) shows that the crystal has a zinc blend structure and reveals the nanoscale crystals size. TEM micrographs show the presence of large particles of Zn(OH)2 (250 nm) and nanometric particles of ZnS (around 15 nm). The spatial distribution of ZnS particles indicates that spinodal decomposition takes place. The solution therefore separates spontaneously into two phases, starting with small fluctuations and proceeding without a nucleation barrier.